Near-Infrared Inorganic Nanomaterials for Precise Diagnosis and Therapy - Li, Wenling; Zhang, Guilong; Liu, Lu (Frontiers in Bioengineering and Biotechnology, 2021)
Traditional wavelengths (400-700 nm) have made tremendous inroads in vivo fluorescence imaging. However, the ability of visible light photon penetration hampered the bio-applications. With reduced photon scattering, minimal tissue absorption and negligible autofluorescence properties, near-infrared light (NIR 700-1700 nm) demonstrates better resolution, high signal-to-background ratios, and deep tissue penetration capability, which will be of great significance for in-vivo determination in deep tissue. In this review, we summarized the latest novel NIR inorganic nanomaterials and the emission mechanism including single-walled carbon nanotubes, rare-earth nanoparticles, quantum dots, metal nanomaterials. Subsequently, the recent progress of precise noninvasive diagnosis in biomedicine and cancer therapy utilizing near-infrared inorganic nanomaterials are discussed. In addition, this review will highlight the concerns, challenges and future directions of near-infrared light utilization.